FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN PERUMAHAN SUBSIDI PADA PT ABSY PROPERTY BANJARMASIN - - Mohdari; Rika Sylvia (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2021)
The problems research concern about the quality of the products offered are not in accordance with the actual condition of the building, the price tends to rise every year so that the down payment issued by consumers is also getting higher and the lack of promotion of housing products so that not many consumers know. This is intended to analyze factors of product quality, price and promotion of the decision to purchase subsidized housing at PT Absy Property, so that it can be processed and presented in the form of systematic, accurate, and justifiable data. The results of this research explain that all variables have a positive effect and the significance of this can be seen from the coefficient of determination (R Square) which reaches 0.268 which means that the remaining 26.8% of 73.2% can be explained by other variables not included in the research model. The conclusion of this research is the analysis of product quality, price and promotion have a positive and significant effect on the decision to purchase subsidized housing at PT Absy Property Banjarmasin.